KONTRIBUSI SEKTOR KEHUTANAN TERHADAP PEREKONOMIAN WILAYAH: KASUS PROVINSI LAMPUNG - Sanudin Sanudin; San Afri Awang; Ronggo Sadono; Dan Ris Hadi Purwanto (Bumi Lestari Journal of Environment, 2015)
One of economy growth indicator is Gross Regional Domestic Product (GRDP).  Theresearch was aimed to know contribution of forestry sector to regional economy in LampungProvince.  Data used were GRDP and Gross Domestic Product (GDP) on 2000 constantmarket prices during 2004 to 2013 period.  Location Quotient (LQ), Multiplier Effect, andShift Share Analysis (SSA) were used in this research.  The results showed that in the period2004-2013, forestry sector is not a basic sector in Lampung Province with LQ value 0.18.Multiplier effect value of forestry sector is 94.92 which means that every additional incomeof Rp Y in the forestry sector will result in added revenue of 94.92 x Rp Y in agriculturesector.  Forestry sector GRDP contributed for 0.38 percent to regional economy of LampungProvince. National growth component of forestry sector in Lampung Province gives a positiveeffect to national growth.  Industrial mix component of forestry sector in Lampung Provinceis slower than national average.  Local share component has a positive value which meansthat the forestry sector in Lampung Province is competitive.